Use Coupon: CART10 and get 10% off on all online Study Material

Total Price: R

There are no items in this cart.
Continue Shopping
Get instant 50% OFF on Online Material.
Use coupon code: MOB50 | View Course list

solve for x; if

log 7(x3+7)-log7(x+3)=2

4 years ago


Answers : (1)


log 7(x3+7)-log7(x+3)=2

log(x3+7)/log7 - logx+3/log7 = 2

logx3+7 - logx+3 = 2log7

logx3+7/x+3 = log49

x3+7 = 49x + 49*3

x3 -49x - 20*7 = 0

x3 - 49x - 140 = 0

now solve for x

4 years ago

Post Your Answer

If x+root y = 11 and root x+y = 7, then how to calculate x and y.
sorry sorry I wrote wrong ya yes x = 9 y = 4
A M S ARUN KRISHNA one month ago
Answer is: X=9, Y=4.
x=9, y=4
Anoopam Mishra one month ago
plz can u give me solution of q48 and q49
q49. Sn will be equal to coff. of x in : (1+1/x) n .(1+x) n = ∑ n C i * n C i+1 (that is power x i+1 from second bracket multiplied by power x i of first, and i varying from 0 to n-1....
Akshay 2 months ago
will be the series in question. n . cofficient of x 2n-2i (-1) j (1+x) i C n = ∑ n -1) 2 q48. Assume ((x+1) Expand (x+1) 2 in LHS and solve. ATB.
Akshay 2 months ago
q48. Assume ((x+1) 2 -1) n = ∑ n C i (1+x) 2n-2i . cofficient of x n will be the series in question. Expand (x+1) 2 in LHS and solve. ATB.
Akshay 2 months ago
x+1/x =1 , x 2 +1/x 2 =2 and x 3 +1/x 3 =3 then x 5 + 1/x 5 = what
x^5 + \frac{1}{x^5} = (x^2 + \frac{1}{x^2})(x^3 + \frac{1}{x^3}) - (x + \frac{1}{x} )"...
Raghu Vamshi Hemadri 28 days ago
x^5 + \frac{1}{x^5} = (x^2 + \frac{1}{x^2})(x^3 + \frac{1}{x^3}) - (x + \frac{1}{x} )"...
Anoopam Mishra one month ago
pa1 one month ago
The plane ax+by+cz=1 meets the co-ordinate axes in A,B and C. The centroid of the triangle is- (3a,3b,3c) (a/3, b/3, c/3) (3/a, 3/b, 3/c) (1/3a, 1/3b, 1/3c) What i am not understanding is...
The correct answer is (D). First of all, it should be clear that a,b,c are not the intercepts of the axes x,y,z resp. If that is true then (a,0,0), (0,b,0) and (0,0,c) should satisfy the eq ...
Yash Jain 9 months ago
please explain Rectangular Hyperbola just visit this link u well get answers of all ur questions PLEASE ..... if u like my answer and my answer is use full for ...
Gayatri Jayesh Bondriya 2 months ago
If u=f(x) and v=g(x) then d(uv)/dx is
its quite simple , rather its product rule for differentiation anyway uv=f(x).g(x) d(uv)/dx = f(x) g , (x) + g(x) f , (x) it is answer APPROVE IF USEFUL
ng29 4 months ago
its very simple first take gx constant and diffrentiade and similarly take fs constant and diffrentiate gx
grenade 4 months ago
hey are you solving integration by parts but all the way answer is d(uv)/dx = f(x) g , (x) + g(x) f , (x)
Gman Namg 4 months ago
View all Questions »
More Questions On Algebra

Ask Experts

Have any Question? Ask Experts

Post Question

Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details